COMMUNITY EMPOWERMENT THROUGH TRAINING FOR VCO (VIRGIN COCONUT OIL) MAKING IN TANGKILING, BUKIT BATU SUB-DISTRICT, PALANGKA RAYA CITY - Yesninopy; Wahidin; Teti Berliani; Mardiana; Defianty; Yusiana (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
The goals of community service can be formulated as follows: Empowering the community, developing environmental potential, Providing knowledge, skills, values and attitudes to mothers so that they become economically productive through training on making VCO (Virgin Coconut Oil) in Tangkiling, Bukit Batu City District Palangkaraya. The community empowerment implementation method used is Participatory Rural Appraisal (PRA). Participatory Rural Appraisal (PRA) is an approach that emphasizes community involvement in all activities. The PRA method aims to make community members become researchers, planners and implementers of development programs and not just objects of development. The methods used in this training are as follows: Lectures and questions and answers are used to provide information about how to make VCO coconut oil for trainees, Demonstrations or demonstrations are used to practice making coconut oil, introducing equipment and materials in making oil Coconut VCO (virgin coconut oil). Results of community service; Community empowerment through training on making VCO (virgin coconut oil) in Tangkiling, Bukit Batu District, was positively responded by the training participants, namely housewives and they were very happy and enthusiastic to participate and be directly involved in the training on making VCO, because they were equipped with knowledge, skills, values and attitudes in the process of making coconut oil and the process of packaging its products. The next result is to make housewives economically productive to continuously make VCO or coconut oil products so that they become superior products in Tangkiling considering that Tangkiling is a tourist spot.